Faktor yang Mempengaruhi Manajemen Laba dimoderasi oleh Ukuran Perusahaan: (Studi pada Perusahaan Perbankan yang Terdaftar di BEI) - Hendi Hendi; Erika Erika (Owner : Riset dan Jurnal Akuntansi, 2022)
Earnings management occurs when there is a separation of positions and a comparison of interests between the owner and the manager. Earnings management is influenced by known independent variables for the purpose of this research. The independent variables used in this study are institutional ownership, managerial ownership, the proportion of independent commissioners, directors, audit committees, audit quality, independent boards, leverage, profitability. The moderating variable used in this research is company size. The dependent variable used in this study is earnings management. The sample that is part of the research is a company that operates in the banking sector and listed in Indonesian Stock Exchange. This study uses secondary data with the banking sector population in 2016-2020 as many as 44 companies and the number of the samples taken based on purposive sampling method is as many as 39 companies with 195 data. The data from this study were processed using two programs, namely SPSS for descriptive statistics and PLS-SEM to prove the accuracy, suitability, and impact of the existing variables. The results of the study found that institutional ownership, managerial ownership, the proportion of independent commissioners, directors, audit committees, audit quality, independent boards, leverage, profitability, firm size were able to have a significant positive effect on earnings management.